The Role of Mass Media in The Emergence of Deviant Behavior in Society - Sinaga, Lianda Rachmadany; Larasati, Ayu (CV. Publikasi Indonesia, 2024)
One of the primary studies in the sociology of communication is the influence of mass communication in society. Media is a communication transmitter or